(untitled) (Journal of Engineering, 2010)
The modern era features the incredible production knowledge by quantum and qualities and with quick changes in theories, interesting practices and even knowledge s view points. In the last years new thinking methods boomed in the mathematical field that refers to chaos theory, this field which continues in growth and evolution quickly in different directions, with all the practical potentiality that carried in large and variety phenomena’s. The tools and the concepts of the theory is considered as a radical cutting with the known mathematical manners that based the modern science since Galileo, Descartes and Newton , and let us see the world in different and radical views, and with the best understanding for its movement powers, its self organization and its evolution. The different concepts of the chaos theory effected in all the knowledge fields and led to unpredictional results in many areas one of them is architecture. Many architectural studies discussed chaos theory and focused on its effects in architectural field through theoretical studying to the theory and its concepts, but the most of these studying didn’t exploit the theory concepts in the formal Generation of the architectural deriving, therefore the research importance came from its trying to answer the important question that the research begins with :( How could new tools be adopted to the Generation of the Architectural forms?), and according to the scientific knowledge that came from the specialized study (architectural & scientific) formulating of the research s problem was:( the lack of knowledge concerning the generating ability of the chaos theory in architecture to generate new forms), therefore the research s aim was to expose the generation ability for chaos theory in architecture to generate new forms. The research tried to build theoretical framework about the vocabularies of the formal Generation according to chaos theory the research reached to formulate three main Generation vocabularies(dynamics- complexity- flexibility) , according to that the research hypothesis was: (could be generate new forms in architectural field through employing chaos theory concepts), the research started reaching its aim through the practical part which reached to formulate special programming with the computer program (Form( to employing the vocabularies of the formal Generation according to chaos theory to generate new architectural forms And finally reached to a group of conclusions that refer to chaos theory and its formal Generation to create new forms in architecture .